CHC and SA applied to the distribution of wind turbines on irregular fields - Bilbao, Martín (2010)
In this article we analyze two kinds of metaheuristic algorithms and random search algorithm applied to distribution of wind turbines in a wind farm. The basic idea is to utilize CHC (a sort of GA) and Simulated Annealing algorithms to obtain an acceptable configuration of wind turbines in the wind farm that maximizes the total output energy and minimize the number of wind turbines used. The energy produced depends of the farm geometry, wind conditions and the terrain where it is settled. In this work, the terrain is irregular and we will analyze two study farm scenarios with a real wind distribution of Comodoro Rivadavia city in Argentina and we will apply both algorithms to analyze the performance of the algorithms and the behavior of the computed wind farm designs.